Hybrid Recommendation System untuk Peminjaman Buku Perpustakaan dengan Collaborative dan Content-Based Filtering - Adrianus Aditya Widjaja; Henry Novianus Palit (Universitas Kristen Petra, 2022)
The development of technology is growing rapidly and followed with the growth of digital data in the internet. Therefore, recommendation system was invented and can be used in many aspects of human life. For example, a book recommendation system can be used to help user to choose a book to be read which is suitable with their preferences. Using a recommendation system can help to reduce the required time to choose a book because of the massive choices of books. This research using hybrid recommendation system which combined collaborative filtering and content-based filtering method. The purpose of this study was to achieve a better recommendation outcome. To measure how well the result of the recommendation, mean reciprocal rank and mean average precision was used. The results showed that weighted hybrid yields a better score than the other two methods. The score was 0.2113 and 0.0988 respectively